Nation’s Ethos in Romanian Literature - Baltatu, Ludmila (Journal of Danubian Studies and Research, 2024)
It is indisputable that the foundation of any national literature is laid by the spiritual life of the people, and the organ of its genuine expression is the people’s language. There is a tight relation between a culture and the landscape within it has been forming. Thus the surrounding nature and historical circumstances have a major part to play in determining a nation’s literature birth and development. All the Romanian literature draws its roots, at one time or another, from our inexhaustible autochthonous folklore, that is, according the the great Romanian poet Mihai Eminescu, an essential ground for the future of our national literary art. Romanian folklore expressions evoking the Danube represent a particular interest due to their amazing spiritual freshness, popular wisdom. The Danube’s magnificence is being lyrically sung as well in Romanian Doinas for centuries.